Agglomeration index: Towards a new measure of urban concentration - Hirotsugu Uchida; Andrew Nelson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
A common challenge in analyzing urbanization is the data. The United Nations (UN) compiles information on urbanization (urban population and its share of total national population) that is reported by various countries but there is no standardized definition of 'urban' resulting in inconsistencies. This situation is particularly troublesome if one wishes to conduct a cross-country analysis or determine the aggregate urbanization status of the regions (such as Asia or Latin America) and the world. This paper proposes an alternative to the UN measure of urban concentration that we call an agglomeration index.
Keywords: R11; O18; 330; agglomeration index; urbanization; accessibility map; cost surface